Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Badan Pusat Statistik Kota Jakarta Selatan - Tiara Febriany; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (International Forum of Researchers and Lecturers, 2024)
Human Resources are a valuable asset and are the focus of every company. Therefore, so that employees can be active at work and have high work morale, companies need something that can motivate their employees, namely by providing support in the form of compensation and work discipline. The purpose of this research is to determine the effect of compensation and work discipline on employee performance at the South Jakarta City Central Statistics Agency. The method used is a quantitative descriptive method. The sampling technique in this research was a saturated sample with a sample size of 60 respondents. Then this research shows that compensation and work discipline simultaneously have a significant effect on employee performance and partially the compensation variable does not have a significant effect while the work discipline variable has a significant effect.